Foreign Body Traumatic Hepatitis In A Lamb - Chellapandian, M.; Arulnathan , N. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A wide range of foreign bodies were reported to occur in the gastrointestinal tract of large and small ruminants (Remi-Adewunmi et al., 2004) which may result in indigestion, development of toxaemic condition and ultimately death. A case of mortality due to traumatic hepatitis associated with severe pneumonia in a lamb caused by accidental ingestion of a neem twig is presented.